Amerykański język praw podmiotowych a demokracja - Raburski, Tomasz (Filozofia Publiczna i Edukacja Demokratyczna, 2014)
The article explores the link between the language of rights and democracy. The author asks whether the dominance of the language of rights in the United States is responsible for the overall condition of American democracy, and the lack of such dominance may have a negative impact on the Polish public sphere. The beginning of the article describes the problems with translating the word „right” from English into Polish. In the next part, the different forms and types of rights are described. Then, a meaning of the „language of rights” is presented. Other languages of public discourse are mentioned for comparison. The consequences and functions of the language of law for the public sphere and democracy are widely discussed. The critical voices about the impact of rights are examined. Finally, the article answers the question about the role of rights in the Polish public sphere and democracy.